Soil restoration after seven years of exclosure management in northwestern Ethiopia - Mekuria, Wolde; Langan, Simon J.; Noble, A.D.; Johnston, Robyn M. (Wiley, 2017)
Ecological restoration through exclosure establishment has become an increasingly important approach to reversing degraded ecosystems in rangelands worldwide. The present study was conducted in northwestern Ethiopia where policy programs are aiming to restore degraded lands. Changes in soil properties following establishing exclosures on communal grazing lands were investigated. A space-for-time substitution approach was used to monitor changes in soil properties after conversion of communal grazing lands to exclosures with ages of establishment ranging from 1 to 7-years. Significant differences in soil pH, exchangeable cations, cation exchange capacity, soil moisture content, and bulk density were observed within exclosures and between exclosures and communal grazing land. Communal grazing land displayed significantly higher soil total nitrogen, phosphorus and potassium compared to exclosures. Exclosures did not display significantly higher soil organic matter content when compared to the communal grazing land. The results confirm that more than 7 years after the establishment of exclosures is required to detect significant improvements in most of the investigated soil properties. Prohibition of the practice of grass harvesting during the first 3 to 5 years following the establishment of exclosure, and decreasing the amount of grass harvest with exclosure age could support to increase easily decomposable organic inputs to the soil and improve soil properties in relatively short period of time.